Safe use of highly steatotic livers by utilizing a donor/recipient clinical algorithm. (2nd September 2013) - Chavin, Kenneth D.; Taber, David J.; Norcross, Melissa; Pilch, Nicole A.; Crego, Heather; McGillicuddy, John W.; Bratton, Charles F.; Lin, Angello; Baliga, Prabhakar K.
Abstract: The aim of this study was to assess the long‐term safety and clinical outcomes associated with the utilization of highly steatotic donor livers utilizing a specific donor/recipient matching algorithm. This was a prospective, observational, single‐center, 10‐yr follow‐up study. Highly steatotic livers were utilized according to a donor/recipient algorithm that guided the surgeon to use highly steatotic donor organs judiciously in low‐risk recipients. This study initially compared fat assessment based on frozen‐section Ehrlich's hematoxylin and eosin (H&E) to reperfusion biopsy fat assessment and demonstrated that H&E is an insensitive analysis to determine degree of steatosis. Patients were divided into three groups based on donor steatosis (group 1: <30% steatosis, group 2: 30–60% steatosis, group 3: >60% steatosis), and clinical outcomes were assessed. One hundred and sixteen patients were included in the analysis. Patients that received severely steatotic livers (>60% fat) showed increased reperfusion liver injury and delayed return of liver function in the early postoperative period, demonstrated by biochemical markers. However, there were no differences in primary non‐function, postoperative complications, length of stay, and patient and graft survival. Using rigorous donor/recipient matching through a detailed algorithm, these data demonstrate that normal liver allograft outcomes are not superior to those in highly steatotic grafts.